An exploratory study on pediatric inguinal hernia videos on the youtube platform - Mehak Sehgal; Divya Jain; Prabudh Goel; Vishesh Jain; Devendra Kumar Yadav; Vivek Verma; Anjan Kumar Dhua (Wolters Kluwer Medknow Publications, 2022)
Aim: A study was conducted to explore the characteristics of the videos on pediatric inguinal hernia repair on YouTube and compare the most popular videos (MPV) with the least popular ones in terms of educative value vis-a-vis their popularity. Materials and Methods: The term "Pediatric inguinal hernia repair" was searched for on YouTube on August 15, 2021, with the filter set to "view rate." Pertinent data were collected from the 50 MPV and the 50 least popular videos (LPV) and then compared. The h-index and affiliation of the surgeon were obtained from the Scopus database, and their affiliation was further categorized as academic or nonacademic. Results: One hundred and seventy-five videos were found with median views of MPV: LPV being 9270 (interquartile range [IQR] - 12099):127 (IQR - 194), respectively (P < 0.0001). Most of the videos in the MPV and LPV groups were uploaded from the United States of America (USA) (MPV - 17 and LPV - 13) and India (MPV - 15 and LPV - 15). The MPV were on YouTube for a median duration of 3.1 (IQR - 5.5) years as compared to 1.2 (IQR - 2.3) years for the LPV (P < 0.0001). Ninety-two surgeons were identified. The median h-index of the surgeons of MPV was 3 (IQR - 12) in comparison to 1 (IQR - 10) of LPV (P = 0.13). The ratio of academic versus nonacademic affiliation among MPV and LPV was almost equal in both the groups. Conclusions: On either end of the spectrum of popularity, the majority of the pediatric inguinal hernia videos on YouTube were surgical videos uploaded from the USA and India. The educative value of these videos was found to be low and widely dispersed. Surgeons from both academic and nonacademic affiliations had contributed similarly.